Modern Problems of Currency Market of RA - Mnatsakanyan, Hayk (Bulletin of Yerevan University G: Economics, 2016)
The current trends, problems and prospects of development of currency exchange market of the Republic of Armenia are presented. The problems that affect the exchange rate are considered. The exchange rate arrangements of IMF are discussed and the influence of currency policy, inflation and trade balance to the exchange rate of Armenian dram is presented.
Keywords: currency market, exchange rates, currency policy, exchange rate arrangement